Kids with special needs information and activities to promote awareness and understanding - Getskow, Veronica; Konczal, Dee.; Armstrong, Beverly (Santa Barbara, Calif. Learning Works, 1996)
Presents both the myths and the facts about disabilities.
"LW 339"--Spine.
Includes bibliographical references.
"Resources and organizations of interest": p. 181-199.
Keywords: Children with disabilities -- Care -- United States; Children with disabilities -- Services for -- United States; Special education -- United States